2015
DOI: 10.1002/oby.21038
|View full text |Cite
|
Sign up to set email alerts
|

Serum betatrophin concentrations are significantly increased in overweight but not in obese or type 2 diabetic individuals

Abstract: Objective: In this study, circulating serum betatrophin levels were quantitated and their relationships with insulin resistance (IR) and other metabolic parameters in Chinese subjects with varying degrees of obesity and glucose tolerance were examined. Methods: Serum betatrophin levels were determined using ELISA in 60 subjects with normal glucose tolerance (NGT: 17 lean, 23 overweight, and 20 obese subjects) and 56 subjects with type 2 diabetes mellitus (T2DM: 14 lean, 23 overweight, and 19 obese subjects). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
77
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 14 publications
9
77
5
Order By: Relevance
“…16,22 In healthy and diabetic patients, the correlation between betatrophin with insulin and HOMA-IR found which contradict with these study findings. 16,17 More recently studies results illustrated that the relation between betatrophin and HOMA-β had a negative correlation both groups. 22,23 However, it was later shown that betatrophin levels had non-significant positive relation with HOMA-β in control healthy or NDM which is not the case in the current study.…”
contrasting
confidence: 69%
See 4 more Smart Citations
“…16,22 In healthy and diabetic patients, the correlation between betatrophin with insulin and HOMA-IR found which contradict with these study findings. 16,17 More recently studies results illustrated that the relation between betatrophin and HOMA-β had a negative correlation both groups. 22,23 However, it was later shown that betatrophin levels had non-significant positive relation with HOMA-β in control healthy or NDM which is not the case in the current study.…”
contrasting
confidence: 69%
“…In reviewing most of the betatrophin articles for different authors, it was apparent that there were different predictor variables of betatrophin in a different status. In contrast, several studies revealed different variables were independently related factors to circulating betatrophin like; c-GT and HOMA-IR, BMI, FT4 and HDL-C, insulin, FPG and HOMA-IR , insulin and HOMA-IR, age and increment of C-peptide and HOMA-IR and LDL-C. 16,21,25,29,39,40 All these predictor variables interpret betatrophin independently. Several of these predictor variables not included in the current study and the others don't have a significant independent prediction for betatrophin.…”
Section: Correlation Between Betatrophin and Uric Acidmentioning
confidence: 91%
See 3 more Smart Citations